Resistance mutations outside the integrase coding region have an effect on human immunodeficiency virus replicative fitness but do not affect its susceptibility to integrase strand transfer inhibitors. - Jan Weber; Justine D Rose; Ana C Vazquez; Dane Winner; Nicolas Margot; Damian J McColl; Michael D Miller; Miguel E Quiñones-Mateu (PLoS ONE, 2013)
Most studies describing phenotypic resistance to integrase strand transfer inhibitors have analyzed viruses carrying only patient-derived HIV-1 integrase genes (INT-recombinant viruses). However, to date, many of the patients on INSTI-based treatment regimes, such as raltegravir (RAL), elvitegravir (EVG), and dolutegravir (DTG) are infected with multidrug-resistant HIV-1 strains. Here we analyzed the effect of drug resistance mutations in Gag (p2/NCp7/p1/p6), protease (PR), reverse transcriptase (RT), and integrase (IN) coding regions on susceptibility to INSTIs and viral replicative fitness using a novel HIV-1 phenotyping assay. Initial characterization based on site-directed mutant INSTI-resistant viruses confirmed the effect of a series of INSTI mutations on reduced susceptibility to EVG and RAL and viral replicative fitness (0.6% to 99% relative to the HIV-1NL4-3 control). Two sets of recombinant viruses containing a 3,428-bp gag-p2/NCp7/p1/p6/pol-PR/RT/IN (p2-INT) or a 1,088 bp integrase (INT) patient-derived fragment were constructed from plasma samples obtained from 27 virologic failure patients participating in a 48-week dose-ranging study of elvitegravir, GS-US-183-0105. A strong correlation was observed when susceptibility to EVG and RAL was assayed using p2-INT- vs. INT-recombinant viruses (Pearson coefficient correlation 0.869 and 0.918, P<0.0001 for EVG and RAL, respectively), demonstrating that mutations in the protease and RT have limited effect on susceptibility to these INSTIs. On the other hand, the replicative fitness of viruses harboring drug resistance mutations in PR, RT, and IN was generally impaired compared to viruses carrying only INSTI-resistance mutations. Thus, in the absence of drug pressure, drug resistance mutations in the PR and RT contribute to decrease the replicative fitness of the virus already impaired by mutations in the integrase. The use of recombinant viruses containing most or all HIV-1 regions targeted by antiretroviral drugs might be essential to understand the collective effect of epistatic interactions in multidrug-resistant viruses.